Impact of occupational stress on organizational performance: case of Mimosa mining company, Zimbabwe - Chigumbu, Gerald (Midlands State University, 2017)
Most mining companies’ performance continues to plummet. The question is that; is it the economy, management and production practises, the business environment or occupational stress which is an obscure problem affecting organizational performance? Could organizational poor performance be traced down to occupational stress? The study sought to assess impact of occupational stress on organisational performance. The study aimed at identifying sources of occupational stress, determining the impact of occupational stress on organizational performance and assess the effectiveness of strategies used to reduce impact of occupational stress on organizational performance at Mimosa Mining Company. The data was collected using questionnaires and interviews. Stratified random sampling was used to select the respondents. An inverse relationship was found between occupational stress and organizational performance. Employees were found to experience occupational stress emanating from the roles they carried out. Demographic variables such as age, job position, experience and income significantly influenced the relationship between occupational stress and organizational performance. The study concluded that occupational stress has negative impact to the organizational performance as it resulted in lost time injuries, absenteeism, accidents, low morale and poor work relations. The study recommends proactive interventions by implementing management strategies that aims on elimination of occupational stress so that the organization may fully achieve optimum organizational excellence.